Starter-generating complex of the gas turbine engine-pumping unit - Барский, Виктор Алексеевич; Маляр, А. В.; Спицын, Владимир Евгеньевич; Боцула, А. Л.; Захаренко, А. Я. (Eastern-European Journal of Enterprise Technologies, 2012)
A starter-generator complex is offered for starting of gas turbine engine generating of electric power, using one asynchronous electric machine and the automatic switching of electrical customers of gascompressor unit on a feed from the starter-generator complex